(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
The Existence and Household Income of Padang Tegal Subak Farmers amidst Tourism Development in Ubud District, Gianyar Regency. The development of tourism in Bali has an impact on land conversion. The area of paddy fields in Bali decreased 537 hectares from 2015 to 2016. This study aims to determine the existence of subak and the income of farmers’ households amidst tourism development in Ubud District, Gianyar Regency. Methods of analysis were used Descriptive qualitative and quantitative. Data were collected using interviews, literature study, survey, observation techniques and all farmers of subak members were selected as survey samples. The results showed that the existence of Subak Padang Tegal persists during the rapid development of tourism. This can be seen from the implementation of the five functions of Subak such as finding and distributing irrigation water, maintenance of irrigation networks, mobilization of resources, conflict management, and religious ritual activities which are still consistently carried out by members of Farmers house hold in Subak Padang Tegal is Rp. 63.039.628 a years, 53% of which comes from non-farm activities. It is suggested that the farmers in Ubud should protect their agricultural land vis-àvis tourism development. The government should pay more attention to the farmers in tourism areas such as subsidies on seed and fertilizer.